Is Pathologic Near-Total Regression an Appropriate Indicator of a Good Response to Preoperative Chemoradiotherapy Based on Oncologic Outcome of Disease?. Issue 50 (December 2015) - Kim, Jee Yeon; Park, In Ja; Hong, Seung Mo; Lee, Jong Lyul; Yoon, Yong Sik; Kim, Chan Wook; Lim, Seok-Byung; Lee, Jung Bok; Yu, Chang Sik; Kim, Jin Cheon
Abstract : Abstract: We evaluated the oncologic outcomes of patients with rectal cancer who demonstrated pathologic near-total regression (NTR) after preoperative chemoradiotherapy (PCRT) and compared with total regression (TR). Pathologic NTR in rectal cancer by tumor regression grade (TRG) is usually considered to indicate a good response, when evaluating tumor response to PCRT. We retrospectively analyzed the outcomes in 263 patients who received PCRT for advanced T3/4 or N+ rectal cancer followed by radical resection. Patients were diagnosed with TR (n = 132) or NTR (n = 131) according to the TRG. Recurrence-free survival (RFS) was evaluated and compared between groups. For evaluating the consistency between the result and previously published data, meta-analysis for summing up survival curve was performed using generalized linear mixed model. ypT status was heterogeneous in the NTR group as follows; 3 Tis (2.3%), 21 T1 (16%), 72 T2 (55%), and 35 T3 (26.7%). Metastatic lymph nodes were more frequently found in the NTR group (6.8% in TR vs 24.4% in NTR patients; P = 0.003). The cumulative recurrence rate was higher in the NTR group (19.8% vs 6.1%; P = 0.003). The 5-year RFS was lower in the NTR group (94% vs 77.8%; P = 0.001). Significant differences in the RFS rate were found in comparison with the published literature. Based on differences in the oncologic outcomes between the TR and NTR groups, it might not be suitable to use NTR as an indicator of good response to PCRT together with TR. Abstract : Supplemental Digital Content is available in the text